Breastfeeding and the risk for diarrhea morbidity and mortality - Victora Cesar; Noiman Adi; Fischer Walker Christa L; Lamberti Laura M; Black Robert E (BMC, 2011)
Abstract Background Lack of exclusive breastfeeding among infants 0-5 months of age and no breastfeeding among children 6-23 months of age are associated with increased diarrhea morbidity and mortality in developing countries. We estimate the protective effects conferred by varying levels of breastfeeding exposure against diarrhea incidence, diarrhea prevalence, diarrhea mortality, all-cause mortality, and hospitalization for diarrhea illness. Methods We systematically reviewed all literature published from 1980 to 2009 assessing levels of suboptimal breastfeeding as a risk factor for selected diarrhea morbidity and mortality outcomes. We conducted random effects meta-analyses to generate pooled relative risks by outcome and age category. Results We found a large body of evidence for the protective effects of breastfeeding against diarrhea incidence, prevalence, hospitalizations, diarrhea mortality, and all-cause mortality. The results of random effects meta-analyses of eighteen included studies indicated varying degrees of protection across levels of breastfeeding exposure with the greatest protection conferred by exclusive breastfeeding among infants 0-5 months of age and by any breastfeeding among infants and young children 6-23 months of age. Specifically, not breastfeeding resulted in an excess risk of diarrhea mortality in comparison to exclusive breastfeeding among infants 0-5 months of age (RR: 10.52) and to any breastfeeding among children aged 6-23 months (RR: 2.18). Conclusions Our findings support the current WHO recommendation for exclusive breastfeeding during the first 6 months of life as a key child survival intervention. Our findings also highlight the importance of breastfeeding to protect against diarrhea-specific morbidity and mortality throughout the first 2 years of life.